First results with collecting probes in U-2M torsatron - Voitsenya, V.S.; Konovalov, V.G.; Ryzhkov, I.V.; Solodovchenko, S.I.; Shtan’, A.F.; Shapoval, A.N.; Maznichenko, S.M. (Вопросы атомной науки и техники, 2018)
The results are presented on a postmortem analysis of the mirror-like SS samples and two glass samples exposed in the Uragan-2M (U-2M) vacuum chamber during experimental campaigns in 2015 and 2016 years. The examination of the samples, after their removal from the chamber, has revealed that all of them were coated with a carbon-containing film of thickness dependent on the sample position. All metal samples were easily cleaned by low energy ions of deuterium plasma, excluding the one located nearby the RF antenna, which was used for RF plasma production.